Sensory interaction between 3‐mercaptohexan‐1‐ol, 3‐isobutyl‐2‐methoxypyrazine and oxidation‐related compounds. (13th March 2015) - Coetzee, C.; Brand, J.; Emerton, G.; Jacobson, D.; Silva Ferreira, A.C.; du Toit, W.J.
Abstract: Background and Aims: Wine aroma is influenced by complex interactions between various wine constituents. This study investigated the sensorial interactive effects of Sauvignon Blanc impact compounds, 3‐mercaptohexan‐1‐ol, 3‐isobutyl‐2‐methoxypyrazine with aldehydes typically originating from oxidation of white wines, methional and phenylacetaldehyde. Methods and Results: Spiked model wines were subjected to sensory descriptive analysis using a trained panel. The concentration of each compound varied from below aroma threshold value to high values reported in wine. Combinations of the four compounds were also evaluated sensorially. Depending on the concentration of the compounds, methional had a strong suppressive effect on the intensity of attributes contributed by 3‐mercaptohexan‐1‐ol, such as grapefruit and guava, whereas methional and 3‐isobutyl‐2‐methoxypyrazine enhanced the intensity of certain attributes, which included cooked beans and cooked potato. Conclusions: Complex sensory interactions may occur between Sauvignon Blanc impact compounds and compounds related to oxidation depending on concentration of the compounds. Oxidation‐derived compounds such as methional can suppress pleasant aroma attributes linked to volatile thiols, while contributing negative attributes especially in the presence of 3‐isobutyl‐2‐methoxypyrazine. Significance of the Study: This study highlights the importance of preserving fresh and fruity flavours while preventing the formation of unwanted aldehydes due to interactions that can influence the overall aroma profile of the wine. This study may also contribute to the sensory characterisation of oxidised Sauvignon Blanc wine.